EVALUASI STANDAR NASIONAL PENDIDIKAN TINGGI PROGRAM STUDI S2 PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI KEAGAMAAN ISLAM - Suprapto, Suprapto (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2019)
AbstractThe potential of Islamic Religious Colleges (PTKI) is to create the competitive and competent generation internationally. The problem now is that PTKI needs to strengthen the academic, such as Human Resources (HR) that qualified and professional; learning that keeps standards; good governance; research and publication; adequate program funding. This study uses a qualitative approach, through observation, interviews, and documentation. The study was conducted in 12 provinces which spread across 10 State Islamic Religious Colleges (PTKIN) and 5 Private Islamic Religious Colleges (PTKIS). The result of this research is the postgraduate management in PTKI under the university and faculty are; The PTKI is not evenly obliging the students to publish their journals before graduate; the average of postgraduate in Islamic religion curriculum is 42 credits; lecturers Homebase do not yet have a special room, they are still in the faculty; the research performance of PTKI lecturers has not been maximized; PTKI lecturer proceedings are still weak to publish the journals in national and international. The interest of postgraduate student in Islamic study program is very high. Recommended: (1) Opening the new of study program either at the faculty or the postgraduate level. It's have to be accompanied by the recruitment of lecturers, so the study program will not lack of lecturers which result in lecturers home based mismatch; (2) providing the number and quality of classrooms, lecture rooms, and acceleration programs for lecturers; (3) allocating adequate lecturer research funds; (4) conduct structured and scheduled thesis guidance; (5) writing and thesis guidance can begin in the second semester. Abstrak Perguruan Tinggi Keagamaan Islam (PTKI) memiliki potensi untuk melahirkan generasi berdaya saing dan berkompetensi internasional. Saat ini PTKI perlu melakukan berbagai penguatan akademik, seperti Sumber Daya Manusia (SDM) yang qualified dan profesional; pembelajaran yang memenuhi standar; tata kelola yang baik; riset dan publikasi; pendanaan program yang memadai. Penelitian ini menggunakan pendekatan kualitatif, melalui observasi, wawancara dan dokumentasi. Penelitian dilakukan di 12 provinsi yang tersebar pada 10 Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) dan 5 Perguruan Tinggi Keagamaan Islam Swasta (PTKIS). Penelitian ini menghasilkan pengelolaan pascasarjana di PTKI dibawah universitas dan fakultas; belum seluruh PTKI mewajibkan mahasiswanya untuk mempublikasikan jurnal sebelum lulus; kurikulum S2 PAI rata-rata 42 SKS; dosen homebase belum memiliki ruangan khusus, masih berada di fakultas; kinerja penelitian dosen PTKI belum maksimal; publikasi pada jurnal nasional, internasional dan prosiding dosen PTKI masih lemah; minat mahasiswa terhadap prodi S2 PAI sangat tinggi. Direkomendasikan: (1) pembukaan prodi S2 baru baik di fakultas atau di pascasarjana harus disertai perekrutan dosen sehingga prodi tidak kekurangan dosen yang berakibat dosen home based mismatch; (2) menyediakan jumlah dan mutu ruang kelas, ruangan dosen, dan program akselerasi bagi dosen; (3) alokasi dana penelitian dosen; (4) melakukan bimbingan tesis secara terstruktur dan terjadwal; (5) penulisan dan bimbingan tesis dapat dimulai pada semester dua.